Re-estimating Ireland's International Innovation Performance - Dermot P. Coates; Keith Fitzgerald (National Competitiveness and Productivity Council (NCPC), 2024)
Ireland's ranking in the Global Innovation Index (GII) stood at 22nd in 2023, a marginal improvement on 2022 (23rd). Ireland ranked 10th among the EU-27. Ireland continues to perform significantly better under innovation outputs (18th) compared to innovation inputs (26th). Ireland last featured in the global top ten in 2018 (ranked 10th) and has a five-year average ranking over 2019-2023 of 18th. Following a recommendation by the NCPC in Ireland's Competitiveness Challenge 2023, this Bulletin re-estimates Ireland's performance in the GII 2023 using GNI* as a measure of national income. This results in a significantly different ranking of Ireland's performance, namely 12th rather than 22nd, with the revised rankings for innovation outputs at 14th and for innovation inputs at 20th. When assessed in terms of GNI*, the gap between Ireland and the best performing countries closes considerably, particularly under 'Business Sophistication' (versus Sweden) and 'Knowledge and Technology Outputs' (versus Switzerland). 'Market Sophistication' remains the most challenging pillar for Ireland.
Keywords: 330